3D Biomimetic in Vitro Model of Self-induced Cardiac Ischemia Based on the Co-culture of Cardiomyocytes Derived from hiPSC and Primary Human Cardiac Fibroblast - Paz Artigas, Laura; González-Lana, Sandra; Polo, Nicolás; Castro-Abril, Héctor; Mazo, Manuel M.; Ochoa, Ignacio; Ciriza, Jesús (Jornada de Jóvenes Investigadores del I3A, 2023)
Large cardiac spheroids (i.e., > 500 µm diameter) that self-induce an ischemic core were generated by co-culture of cardiomyocytes derived from induced pluripotent cells (hiPSC-CMs) and primary cardiac fibroblast (hCF). Without modification of culture conditions, spheroids’ large size allowed the recreation of a dead core, fibrotic remodelling and tissue stiffening.